2013
DOI: 10.1093/hmg/ddt316
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of Best disease causing missense mutations on bestrophin-1 trafficking

Abstract: Mutations in bestrophin-1 (Best1) cause Best vitelliform macular dystrophy (BVMD), a dominantly inherited retinal degenerative disease. Best1 is a homo-oligomeric anion channel localized to the basolateral surface of retinal pigment epithelial (RPE) cells. A number of Best1 mutants mislocalize in Madin-Darby canine kidney (MDCK) cells. However, many proteins traffic differently in MDCK and RPE cells, and MDCK cells do not express endogenous Best1. Thus, effects of Best1 mutations on localization in MDCK cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
56
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(63 citation statements)
references
References 43 publications
(70 reference statements)
7
56
0
Order By: Relevance
“…4 B, C, and G). In addition, coexpression of AQP1/hBEST1 and BEST1-A243V also leads to significant reduction in VRAC currents, in agreement with a dominant-negative mode of action of BEST1 mutations on wild-type BEST1, as suggested earlier (37).…”
Section: Best1 Deficiency In the Mouse Impairs Sperm Function And Ressupporting
confidence: 86%
“…4 B, C, and G). In addition, coexpression of AQP1/hBEST1 and BEST1-A243V also leads to significant reduction in VRAC currents, in agreement with a dominant-negative mode of action of BEST1 mutations on wild-type BEST1, as suggested earlier (37).…”
Section: Best1 Deficiency In the Mouse Impairs Sperm Function And Ressupporting
confidence: 86%
“…6 Monomers of Best1 have four transmembrane domains as well as intracellular N-and C-termini, with the latter being at the terminus of a large, cytosolic domain. [7][8][9] Monomers of Best1 oligomerize [10][11][12][13][14] to form a highly conserved homopentameric Ca 2ĂŸ -activated ion channel. 8,9 Data from heterologous systems, 15,16 primary human RPE cell culture, 17,18 mouse models, 19,20 the structurally similar paralog bestrophin-2, 21,22 as well as recently published crystal structures 8,9 all unambiguously demonstrate that mammalian Best1 is a calcium-activated anion channel.…”
Section: Discussionmentioning
confidence: 99%
“…We maintained HEK293 and MDCK II cells (American Type Culture Collection, Manassas, VA, USA) as previously described 10,11 : in a 95% air 5% CO 2 environment at 378C. Transfections were carried out as before 10,11,17 using a commercial reagent (Lipofectamine; Invitrogen, Carlsbad, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the stoichiometry was unknown (Johnson et al, 2013) but was expected to be between four and six subunits per channel (with the mass of a channel-Fab complex therefore being of the order of 300-500 kDa), it was concluded that perhaps the difficulty in phasing with bromide or selenium was owing to the large number of relatively weak sites produced by these derivatives, and phasing may be made possible by using a large cluster compound that could bind at a single site per subunit or even per channel. The only heavy-atom cluster tested for this protein crystal was tantalum bromide (Ta 6 Br 12 ÁBr 2 ), but several others are now commercially available, including the magic triangle (Beck et al, 2009) and tungsten-cluster salts (Rudenko et al, 2003), that may be useful in similar circumstances by the same rationale.…”
Section: Phasing With Tantalum Bromide 41 Derivatization With Tantamentioning
confidence: 99%